2012
DOI: 10.1042/cbi20090329
|View full text |Cite
|
Sign up to set email alerts
|

Retention and transmission of active transcription memory from progenitor to progeny cells via ligand‐modulated transcription factors: elucidation of a concept by BIOPIT model

Abstract: Observations made in live cells have clearly demonstrated that agonist-activated steroid/nuclear receptors reorganize in the nucleoplasm into hundreds of discrete speckled structures commonly referred to as nuclear foci. Subsequent studies have shown that nuclear foci are formed only with agonist- and not with pure antagonist-bound receptors. Also, the other accessory components of transcriptional machinery co-localize in nuclear foci with the activated receptors, suggesting these to be active gene transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In order to sustain the inheritance of gene expression and biological functions, epigenetic mechanisms are linked to the transmission of cell lineage and phenotype from progenitor to progeny. These modifications are now known to be transmitted to the progeny cells with the epigenetic marks or genome bookmarking by transcription factors and other gene regulatory proteins ( 137 , 138 ). The deviation from the transmission of normal epigenetic marking is suggested to be relevant not only in cell differentiation but also in the onset of several diseases, including cancer.…”
Section: Omics Of the Head And Neck Cancermentioning
confidence: 99%
“…In order to sustain the inheritance of gene expression and biological functions, epigenetic mechanisms are linked to the transmission of cell lineage and phenotype from progenitor to progeny. These modifications are now known to be transmitted to the progeny cells with the epigenetic marks or genome bookmarking by transcription factors and other gene regulatory proteins ( 137 , 138 ). The deviation from the transmission of normal epigenetic marking is suggested to be relevant not only in cell differentiation but also in the onset of several diseases, including cancer.…”
Section: Omics Of the Head And Neck Cancermentioning
confidence: 99%
“…Toxicants include industrial chemicals, such as dioxine and polychlorite biphenyles pesticides, and pharmaceutical products, e.g., cytostatic drugs that block gene transcription and may cause permanent damage in blastocysts. Even pre- and peri-conceptional exposures are associated with disease in the offspring through interfering with meiotic and/or mitotic cell cycles ( 10 , 11 ). For example, alterations of temporal and spatial patterns of meiotic DNA replication are induced through involvement of proteins SMC1β, RAD21L, and STAG3 of the TET1-regulated replication machinery by complex cohesion links between meiosis and ­cancer ( 12 ).…”
Section: Gene Translation In Cancer Etiologymentioning
confidence: 99%
“…Considering that these residues serve a role in both acetylation and binding to importin‐α, it is important to explore how mutations within this region and other parts of the hinge region of AR influence the subsequent association with mitotic chromatin. Determination of the mechanism for the mitotic chromatin association of AR and its mutants will not only provide us with the potential targets of androgen‐mediated regulation, but also contribute to our understanding of the influence that androgens have on AR‐related diseases .…”
Section: Introductionmentioning
confidence: 99%
“…It was postulated that the docking of NRs to the condensed mitotic chromatin platform has important physiological ramifications. In this context, gene book‐marking and BIOPIT (biomolecular imprints offered to progeny for inheritance of traits) hypotheses were proposed to explain the physiological significance of the mitotic chromatin association of transcription factors . It was reported that, during mitosis, ‘interphase nuclear foci’ co‐migrate with condensing chromatin as transcription units to the progeny cells, ensuring that the progenitor cells transmit a biomolecular blueprint of transcription status to subsequent generations to express and sustain their characteristic proteome .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation